Studies on water quality and pathogenic bacteria in coastal water Langkawi, Malaysia - Khan Chowdhury, Ahmed Jalal; Nordin, Noor Faizul Hadry; M., Azrul Naim; John, Akbar; Yunus, Kamaruzzaman (Triveni Enterprises, Lucknow (India), 2012)
A study on physico-chemical parameters and pathogenic bacterial community was carried out at the coastal waters of Pulau Tuba island, Langkawi. The physico-chemical parameters such as temperature (27.43-28.88 degrees C), dissolved oxygen (3.79-6.49 mg l(-1)), pH (7.72-8.20), salinity (33.10-33.96 ppt), total dissolved solids (32.27-32.77 g l(-1)) and specific conductivity (49.83-51.63 mS cm(-1)) were observed. Station 3 and station 4 showed highest amount of nitrates (26.93 and 14.61 microg at N l(-1)) than station 1 (2.04 microg at N l(-1)) and station 2 (4.18 microg at N l(-1)). The highest concentration (12.4 +/- microg l(-1)) of chlorophyll a was observed in station 4 in October 2005. High phosphorus content (561 microg P l(-1)) was found in the station 2. Thirteen bacterial isolates were successfully identified using API 20E system. The highest amount of bacteria was observed at Station 4 (3400 CFU ml(-1)) and the lowest numberwas at Station 2 (890 CFU ml(-1)). Out of identified 13 Gram-negative bacterial isolates dominant species were Aeromonas hydrophila, Klebsiella oxytoca, Pseudomonas baumannii, Vibrio vulnificus, Proteus mirabilis, Providencia alcalifaciens and Serratia liquefaciens. Apart from this, oil biodegrading Pseudomonas putida were also identified. The study reveals the existing status of water quality is still conducive and the reasonably diverse with Gram-negative bacteria along the Pulau Tuba Langkawi.